Implications of the use of plastic shelters in the initial performance of Nothofagus pumilio plantations in Torres del Paine National Park Implicancias del uso de protecciones plásticas en el desempeño inicial de plantaciones de Nothofagus pumilio en el Parque Nacional Torres del Paine - Salinas, Patricio E.; Bannister, Jan R.; Vidal Ojeda, Osvaldo Javier (My University, 2022)
Environmental changes caused by fires in forest ecosystems can hinder reforestation processes, since it is necessary to have a cover that provides lateral protection. One solution to this problem has been the incorporation of tree shelter; however, there is evidence both for and against their use. The objectives of this study are to compare the initial performance (in terms of survival, growth and browsing) in Nothofagus pumilio plantations with and without the use of tree shelters in Torres del Paine National Park and to evaluate associated costs and operational yields involved in the use of this protections. Survival, growth and browsing variables were measured for 194 experimental units in three sectors of the park. The findings show that after four years, there are significant differences in survival and growth, being higher for plants with shelter. Browsing was also less likely under protected conditions. However, planting management and operational costs related to protections showed 51,6% additional costs and 14% loss of protections aesthetically affecting natural areas of the park. In consideration of the above, we conclude that the use of tree shelter favors a better performance in N. pumilio, however, we recommend that for a sustainable management of restoration actions, especially within wild areas, the financial, operational and environmental aspects associated with the use of tree shelter should be considered and counterbalanced.
Keywords: browsing; ecological restoration; nothofagus pumilio; tree shelter